Nursing diagnoses and care assessed by the patients treated with percutaneous coronary intervention due to acute coronary syndrome - Szabla, Zofia; Reczek, Agata; Brzostek, Tomasz; Kawalec, Ewa; Malinowska-Lipień, Iwona; Gabryś, Teresa (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. At present, the most effective method of treatment for acute coronary syndromes (ACS) is the promptest possible canalisation of the infarct-related vessel by means of the percutaneous coronary intervention method (PCI), which also affects the mode of nursing procedure. There is currently no functional model of care with regard to post-PCI patients, while previous attempts at implementing it have failed to include verification of patients’ opinions. Aim. The purpose of the work was to indicate what problems of biopsychosocial nature occurred among post-PCI patients and to what extent they were resolved by the nurses. Material and methods. 100 ACS-affected patients treated with the PCI method were subjected to the study. The study utilised data collected on the basis of a survey questionnaire, medical records, and direct observation. Results. It follows from the obtained data that the major problems occurring among post-PCI patients included: pain complaints, dyspnea, difficult urination, weakness, increased thirst, disturbed sleep rhythm, fear and anxiety, insufficient knowledge relating to disease risk factors. The patients were satisfied with nursing care involving the fulfillment of their biological needs, while significantly less with emotional and value-oriented support. 88% of the subjects reported an absence of health-related information and education. Conclusions. Among the patients treated with the PCI method due to the ACS causes, a high level of satisfaction was found with regard to nursing activities aimed at resolving biological problems. Improvements in the areas of emotional support, information, and health education are required.